Abu Hayyân's Interpretation of the Verses of Law (Study of the Verse of the Relationship between Husband and Wife in Verse Qs. Al-Baqarah [2]: 222) - Romlah Widayati; Saepullah (Contemporary Quran, 2025)
This research examines Abu Hayyan's methodology in the tafsir 'al-Bahr al-Muhit,' especially in interpreting QS. Al-Baqarah [2]: 222, by comparing mutawatir and shādzdzah qirât. Abu Hayyan's approach highlights the interaction between qirât and legal interpretation and compares it with other scholars to assess his contribution to Islamic jurisprudence. This study is qualitative research using descriptive-analytical methods. It analyses Abu Hayyan's interpretation, especially in his work al-Bahr al-Muhit, by comparing the different interpretations of other scholars to gain a broader insight. This study concludes that Abu Hayyân succeeded in showing that qirât syâdzdzah can be used to interpret the Qur'an. Qirât shâdzdzah can be compromised with qirât mutawatir to provide a more holistic interpretation in the study of interpretation and Islamic jurisprudence.